Diagnostic and therapeutic approach to acute blood pressure elevations: results of an international survey among excellence centres of the European society of hypertension - Giacomo Buso; Thomas Weber; Christos Fragoulis; Guido Grassi; Claudia Agabiti-Rosei; Christian Delles; Michalis Doumas; Massimo Salvetti; Reinhold Kreutz; Konstantinos Tsioufis; Maria Lorenza Muiesan (Blood Pressure)
Background Acute blood pressure (BP) elevations are common in emergency settings and are traditionally classified into hypertensive urgencies (HU) and hypertensive emergencies (HE). Malignant hypertension (MHT) represents a severe form of HE characterised by small vessel damage. Although international guidelines provide clear definitions and treatment strategies, real-world data have shown persistent fragmentation and heterogeneity in the diagnosis and management of these patients.Methods A web-based, anonymous survey promoted by the European Society of Hypertension (ESH) was distributed among physicians from 18 European and 4 non-European countries. The questionnaire assessed definitions, diagnostic work-up, BP measurement practices, and therapeutic strategies for HU, HE, and MHT.Results Sixty–four participants in 56 centres completed the survey. HU was correctly defined as a severe BP elevation without acute clinically symptomatic hypertension-mediated organ damage (A-HMOD) by 45.3% of respondents. Small cuffs were available to 79.7% and extra-large cuffs to 70.3% of respondents.. Intravenous antihypertensive therapy was used for HE by 88.7% of participants, while 20.6% also used intravenous drugs for HU. Parenteral clonidine and sublingual nifedipine were prescribed by 29.7% and 26.6% of respondents, respectively. Definitions and therapeutic approaches for MHT varied substantially, with 62.9% adopting a recently proposed definition involving at least three target organ damages in patients with BP >200/120 mmHg.Conclusions This international survey highlights considerable variability in the definition, diagnostic work-up, and therapeutic management of acute BP elevations, emphasising the need for harmonised protocols and further education.